TO THE MOON AND BACK: THE ADAPTATION OF MOON AS SYMBOL IN MOON KNIGHT'S COMIC TO TELEVISION SERIES ADAPTATION - Dimas Misbahul Munir; Dian Leoni Andri; Fadhilah Desy Handayani; Gusti Faradila Indrayani; Hadyan Rosyad; Mariam Kusniah; Tatik Apriliya; Yanti Indah Suryani (UIN Raden Mas Said Surakarta, 2023)
Moon Knight is one of the best-selling series in Marvel Studios, and no studies discussed the moon's symbolism in the comic Moon Knight and the TV series adaptations. This paper focuses on a shift in the meaning of the symbol from comics to TV series adaptations. In this research, the qualitative descriptive study is done to reveal whether the TV series adaptation of Moon Knight story faithfully reflects the moon symbolism in the comics. The research uses Hutcheon’s adaptation theory as background to analyze symbol adaptation, from the comic to TV series, and Eliade symbol theory to discuss the shift in the meaning of the symbols. The theory of Dissociative Identity Disorder from Kluft is used to analyze the three characters appear in the one body of the Moon Knight. Using Spradley's analysis method, we conclude that there are differences between the story from the Comic Moon Knight and its TV series adaptation. There were deficiencies that did not fully reflect the moon, and three symbols in the scene were unrelated to each other. The benefit of this research is to find out the significance of the differences in symbols in the adaptation of the Moon Knight series and to become reference material for future researchers who want to discuss the symbolization of the moon in the Moon Knight film.